2012
DOI: 10.1161/hypertensionaha.112.193870
|View full text |Cite
|
Sign up to set email alerts
|

Renal Hemodynamics and Renal Function After Catheter-Based Renal Sympathetic Denervation in Patients With Resistant Hypertension

Abstract: Abstract-Increased renal resistive index and urinary albumin excretion are markers of hypertensive end-organ damage and renal vasoconstriction involving increased sympathetic activity. Catheter-based sympathetic renal denervation (RD) offers a new approach to reduce renal sympathetic activity and blood pressure in resistant hypertension. The influence of RD on renal hemodynamics, renal function, and urinary albumin excretion has not been studied. One hundred consecutive patients with resistant hypertension wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
152
0
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 285 publications
(175 citation statements)
references
References 34 publications
8
152
0
15
Order By: Relevance
“…In our study cohort, calculated RVR (using renal perfusion assessed by MRI-ASL and brachial mean arterial pressure) was significantly reduced 3 months after RDN, indicating reduced resistance in renal vascular bed. These data are in accordance with another report relying on duplex ultrasonography that found a decreased renal resistive index after 6 months of RDN, indicating reduced intraparenchymal resistance (30). Thus, in this study we observed that renal perfusion did not change acutely or after 3 months of RDN ( Figure 1).…”
Section: Discussionsupporting
confidence: 93%
“…In our study cohort, calculated RVR (using renal perfusion assessed by MRI-ASL and brachial mean arterial pressure) was significantly reduced 3 months after RDN, indicating reduced resistance in renal vascular bed. These data are in accordance with another report relying on duplex ultrasonography that found a decreased renal resistive index after 6 months of RDN, indicating reduced intraparenchymal resistance (30). Thus, in this study we observed that renal perfusion did not change acutely or after 3 months of RDN ( Figure 1).…”
Section: Discussionsupporting
confidence: 93%
“…However, it has been shown that systolic BP at baseline is correlated to BP lowering after the procedure. 2 This is supported by the finding that patient no. 3 with a baseline BP of 222/101 mm Hg, apparently suitable according to present recommendations, 3,4 experienced a pronounced reduction by 66/29 mm Hg.…”
mentioning
confidence: 73%
“…Амбу-латорное и домашнее АД снижается не очень сильно; описано уменьшение потребности в антигипертен-зивных препаратах [627]. Получены также некото-рые данные о дополнительной пользе метода в виде, например, уменьшения артериальной жесткости, обратного развития ГЛЖ и диастолической дис-функции, ренопротекции и улучшения толерантно-сти к глюкозе [628][629][630]. За исключением редко воз-никающих проблем с катетеризацией (местная гема-тома, травма сосуда и т.…”
Section: денервация почекunclassified